Chloroplast lipid biosynthesis is fine-tuned to thylakoid membrane remodeling during light acclimation. Issue 1 (18th November 2020) - Yu, Linhui; Fan, Jilian; Zhou, Chao; Xu, Changcheng
Abstract: Reprogramming metabolism, in addition to modifying the structure and function of the photosynthetic machinery, is crucial for plant acclimation to changing light conditions. One of the key acclimatory responses involves reorganization of the photosynthetic membrane system including changes in thylakoid stacking. Glycerolipids are the main structural component of thylakoids and their synthesis involves two main pathways localized in the plastid and the endoplasmic reticulum (ER); however, the role of lipid metabolism in light acclimation remains poorly understood. We found that fatty acid synthesis, membrane lipid content, the plastid lipid biosynthetic pathway activity, and the degree of thylakoid stacking were significantly higher in plants grown under low light compared with plants grown under normal light. Plants grown under high light, on the other hand, showed a lower rate of fatty acid synthesis, a higher fatty acid flux through the ER pathway, higher triacylglycerol content, and thylakoid membrane unstacking. We additionally demonstrated that changes in rates of fatty acid synthesis under different growth light conditions are due to post-translational regulation of the plastidic acetyl-CoA carboxylase activity. Furthermore, Arabidopsis mutants defective in one of the two glycerolipid biosynthetic pathways displayed altered growth patterns and a severely reduced ability to remodel thylakoid architecture, particularly under high light. Overall, this study reveals how plants fine-tune fatty acid and glycerolipid biosynthesis to cellular metabolic needs in response to long-term changes in light conditions, highlighting the importance of lipid metabolism in light acclimation. Abstract : Lipid metabolism is fine-tuned to cellular metabolic demands during thylakoid membrane remodeling in response to long-term changes in light intensity.